Public Education to Maintain the Quality of Population Data - Mardianto; Pradipta, Anjar; Nurtanzis Sutoyo, Muh.; Paliling, Alders (Digital Innovation, 2024)
Community service is an effort to apply science and knowledge in solving problems faced by society. One important aspect of community service is maintaining population data. Accurate and up-to-date population data is very important for development planning, public policy and various other purposes. Population data is a type of data that has strategic value in development planning, public services, social policy and various other activities. However, there are challenges in managing and maintaining population data so that it remains accurate, reliable and can be accessed easily. Community service is needed in the form of maintaining population data to support the efficiency and effectiveness of data use. Community service regarding the maintenance of population data is an important step in supporting sustainable community development. With accurate and well-maintained population data, public policies and development programs can be implemented more effectively. Through outreach, education and training approaches, the community can actively participate in maintaining the accuracy of their population data. It is hoped that this community service can continue and have a positive impact in the long term